2021
DOI: 10.1111/jvh.13524
|View full text |Cite
|
Sign up to set email alerts
|

Sustained and cumulative impact of an electronic medical record‐based alert on a hepatitis C birth cohort screening programme

Abstract: Routine HCV antibody testing of birth cohort patients was endorsed by the CDC and the USPSTF nearly one decade ago. 1,2 Despite these recommendations, screening rates in the United States have remained low, 3 prompting a variety of interventions to increase screening and uptake rates in the target population. 4 We recently reported the short-term results of a system-wide, electronic medical record-based best practice alert (BPA). We found a significant increase in screening rates (SR) in response to the alert.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Over the past years, the majority of baby boomer patients have been screened, and continued screening can be expected to result in a further increase in the screening rate. Thus, our study demonstrates the feasibility and potential impact of this approach at the health system level 6,7…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Over the past years, the majority of baby boomer patients have been screened, and continued screening can be expected to result in a further increase in the screening rate. Thus, our study demonstrates the feasibility and potential impact of this approach at the health system level 6,7…”
Section: Discussionmentioning
confidence: 61%
“…Thus, our study demonstrates the feasibility and potential impact of this approach at the health system level. 6,7 FIGURE 3 Response to Antiviral Therapy a Abbreviations: ITT, intention to treat; SVR, sustained virologic response. a The figure shows the SVR rates in patients whose infection was newly identified through birth cohort screening (blue) and in patients with known infection who were referred for treatment (white).…”
Section: Discussionmentioning
confidence: 99%
“…Our BPAs were designed to identify already tested HCV seropositive individuals and appropriately engage them in care at the TOHVHP, irrespective of risk factor(s). In the majority of previously conducted studies in which EMRs were used to identify and link individuals living with HCV to care, BPAs were configured to recommend screening serology to identify people living with HCV based on either the birth cohort or risk-based screening strategies (13)(14)(15)(16)(17)(18)(19)(20). A review of studies found that, by using a riskbased approach for HCV screening, only half of the people living with HCV were ultimately made aware of their status (25).…”
Section: Patient Profilesmentioning
confidence: 99%